Kepemimpinan dalam Mengembangkan Budaya Hidup Bersih: Studi Kasus Mts Darul Ishlah Lubuklinggau - Laila Wulandari; Andi Arif (Universitas Pahlawan Tuanku Tambusai, 2023)
This research is based on the role of leadership in developing a culture of cleanliness that exists in an Mts Darul Ishlah, where leadership is required to be wise in developing a culture of clean living at Mts Darul Ishlah in order to develop a culture that has been applied from the past, where the principal is expected to have the ability in the way of development that will be carried out according to existing programs. The methods used are descriptive qualitative, data collection techniques with interviews, observations, documentation related to planning and implementation in the field. The subjects of the study were the principal and then from informants namely from the principal, teachers, students and hygiene sie at Mts Darul Ishlah. The results showed that there was a written program, there was writing about cleanliness that was placed in various places, and reflected the values of clean living in accordance with existing rules, and there were punishments and rewards for students who did not follow the existing program rules. While in the Institute shows leadership in the Institution has a few obstacles that must be solved, and the need for cooperation between all members in the Institution, and the need for significant changes that are expected so that the recommended program can be implemented as well as possible.